2008
DOI: 10.1007/s11227-008-0191-3
|View full text |Cite
|
Sign up to set email alerts
|

The load balancing problem in OTIS-Hypercube interconnection networks

Abstract: An interconnection network architecture that promises to be an interesting option for future-generation parallel processing systems is the OTIS (Optical Transpose Interconnection System) optoelectronic architecture. Therefore, all performance improvement aspects of such a promising architecture need to be investigated; one of which is load balancing technique. This paper focuses on devising an efficient algorithm for load balancing on the promising OTIS-Hypercube interconnection networks. The proposed algorith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…Furthermore the reached outcome and the issued results of the simulation from Zaho et al of the proposed algorithms on load balancing has shown a considerably big improvements in enhancement in redistribution the load balancing of the processors of the topology [12]. In a different literature and research done by Zaho and Xiao they investigated a different algorithm named t DED-X for load balancing on homogeneous optoelectronic technology and they proposed new algorithm framework, Generalized Diffusion-Exchange-Diffusion Method, this framework was efficient for the load balancing distribution on the Heterogeneous optoelectronic technology [11,13,14].…”
Section: Background and Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore the reached outcome and the issued results of the simulation from Zaho et al of the proposed algorithms on load balancing has shown a considerably big improvements in enhancement in redistribution the load balancing of the processors of the topology [12]. In a different literature and research done by Zaho and Xiao they investigated a different algorithm named t DED-X for load balancing on homogeneous optoelectronic technology and they proposed new algorithm framework, Generalized Diffusion-Exchange-Diffusion Method, this framework was efficient for the load balancing distribution on the Heterogeneous optoelectronic technology [11,13,14].…”
Section: Background and Related Workmentioning
confidence: 99%
“…During the last two decades a big number of interconnection networks for High Speed Parallel Computers (HSPC) investigations are proposed in literature [6,13,15]. As an example one of these networks was the hypercube interconnection network [8,13].…”
Section: Definitions and Topological Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…It balances the workload for every two processors connected via every dimension d, where 1 ≤ d ≤ n on an n-Cube by transferring the extra load at each processor to its neighbor via the dimension d. DEM presented an improvement solution to the load balancing problem by redistributing the workload among processors without the need of global information of such workload. Furthermore, the worst-case diversity size of workload among processors for this technique is log2n on an n-Cube, where the diversity size is defined as the difference between the minimum and the maximum workload size assigned to each processor [11].…”
Section: Load Balancingmentioning
confidence: 99%
“…We have used common parameters that are usually used to measure the effect of load balancing techniques on the performance of parallel processing systems; the used parameters are load balancing accuracy, execution time, speed, and number of communication steps. These parameters were presented in [11]; this section also aims to compare our model using FOFEM with the CDEM model introduced in [11] because CDEM is the only load balancing algorithm proposed for OTIS-n-Cube topology and also showed its superiority over pervious methods for hypercube topologies.…”
Section: Analytical Evaluationmentioning
confidence: 99%